Understanding semantics-based decision support - Jain, Sarika (Boca Raton, FL : Chapman & Hall/CRC, 2020)
This book is an attempt to establish in the readers the importance of creating interoperable data stores and writing rules for handling this data. It also covers extracts from a few project dissertations and a research funded project that the author had supervised. Describes the power of ontologies for better data management Provides an overview of knowledge engineering including ontology engineering, tools and techniques Provides sample development procedures for creating two domain ontologies. Depicts the utility of ontological representation in situation awareness Demonstrates recommendation engine for unconventional emergencies using a hybrid reasoning approach. The text explains how to make better utilization of resources when emergency strikesGraduates and undergraduates doing courses in artificial intelligence, semantic web and knowledge engineering will find this book beneficial.
OCLC-licensed vendor bibliographic record.
Keywords: Decision making; Database management; Knowledge management; COMPUTERS / Artificial Intelligence; COMPUTERS / Database Management / Data Mining; COMPUTERS / Machine Theory